СППР по формуванню кредитного портфеля комерційного банку - Moskalenko, V. V.; Zamozdra, A. A. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
The problem of formation of an optimum credit portfolio is considered. An algorithm of formation of a portfolio for the first interval under consideration and projects of portfolios for the subsequent intervals of the planning period is offered. Description of the Decision Support System for formation of a credit portfolio and delivery of credits to physical and legal persons is resulted.